The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2005
DOI: 10.1063/1.1849798
|View full text |Cite
|
Sign up to set email alerts
|

Electron-beam-generated x rays from X pinches

Abstract: X pinches are well known to produce very small, dense plasma pinches (“micropinches”) that emit short bursts of 1.5–8keV radiation [Shelkovenko et al., Phys. Plasmas 9, 2165 (2002)]. X-ray radiation in the 8–100keV range is also emitted, only a small portion of which is associated with the micropinches. Beginning immediately after the soft x-ray burst, higher energy x-ray emission is observed that is attributed to energetic electrons accelerated in the gaps that appear in the X-pinch plasma structure. The temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
35
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 17 publications
0
35
0
Order By: Relevance
“…On the other hand the hard x-ray images (Eγ>11 keV) made with an Al filter 400µm thick have very different quality. In the case of the standard X pinch, the contrast and spatial resolution of the images are very low as was typically observed with standard X pinches in the past [4,5]. In the HXP image, the mesh is clearly seen and spatial resolution is much better.…”
Section: Experimental Setup and Resultsmentioning
confidence: 81%
See 2 more Smart Citations
“…On the other hand the hard x-ray images (Eγ>11 keV) made with an Al filter 400µm thick have very different quality. In the case of the standard X pinch, the contrast and spatial resolution of the images are very low as was typically observed with standard X pinches in the past [4,5]. In the HXP image, the mesh is clearly seen and spatial resolution is much better.…”
Section: Experimental Setup and Resultsmentioning
confidence: 81%
“…Higher energy X-ray radiation in the 8-100 keV range is also emitted [4,5]. In a standard X-pinch, beginning immediately after the soft X-ray burst, this higher energy ("hard") X-ray radiation is emitted which is attributed to energetic electrons accelerated in the gap that develops in the plasma at the X-pinch cross point immediately after the X-ray burst.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic pressure compresses the wire/plasma, and it can be further imploded by self-magnetic pressure. Radiation energy W r > 500 mJ was observed in the range 1.2-1.5 keV and W r > 20 mJ in the energy range 3-5 keV [1,2].…”
Section: Introductionmentioning
confidence: 96%
“…The emission of hard x-rays (HXR) with photon energies greater than 5 keV is a common feature in Z-pinch discharges such as vacuum sparks [1][2][3], plasma focus [4,5], gas-puff [6,7], X-pinch [8][9][10][11] and wire array [12][13][14][15][16]. The previous studies showed that X-pinch had emitted HXR continuum and characteristic line radiations due to interaction of energetic electron beams with matter [11].…”
Section: Introductionmentioning
confidence: 99%